2012
DOI: 10.1155/2012/728397
|View full text |Cite
|
Sign up to set email alerts
|

Burden of Human Papillomavirus among Haitian Immigrants in Miami, Florida: Community-Based Participatory Research in Action

Abstract: Background. Haitian immigrant women residing in Little Haiti, a large ethnic enclave in Miami-Dade County, experience the highest cervical cancer incidence rates in South Florida. While this disparity primarily reflects lack of access to screening with cervical cytology, the burden of human papillomavirus (HPV) which causes virtually all cases of cervical cancer worldwide, varies by population and may contribute to excess rate of disease. Our study examined the prevalence of oncogenic and nononcogenic HPV type… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
22
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 30 publications
3
22
0
1
Order By: Relevance
“…Our findings on patient acceptability of HPV self-sampling are consistent with data among other vulnerable groups and similar to our prior findings among a community-based sample of Haitian women. 37,[40][41][42][43][44] We also found that Haitian women at CHS were more likely to choose HPV self-sampling than Latinas at ACC. Our prior work has shown that Haitian women have much less familiarity and experience with Pap smear than Latinas.…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…Our findings on patient acceptability of HPV self-sampling are consistent with data among other vulnerable groups and similar to our prior findings among a community-based sample of Haitian women. 37,[40][41][42][43][44] We also found that Haitian women at CHS were more likely to choose HPV self-sampling than Latinas at ACC. Our prior work has shown that Haitian women have much less familiarity and experience with Pap smear than Latinas.…”
Section: Discussionsupporting
confidence: 55%
“…Our prior work has shown that Haitian women have much less familiarity and experience with Pap smear than Latinas. [42][43][44] However, financial considerations may have also played a role in why more Haitian women chose HPV; at CHS women have to pay separately for a Pap smear (based on a sliding fee scale) while at ACC the service is included when done as part of the visit. We also found that HPV prevalence among the participants varied by ethnicity with Haitian participants demonstrating a higher prevalence than Latinas, whose prevalence was notably lower than previously measured in a national sample.…”
Section: Discussionmentioning
confidence: 99%
“…As noted previously, foreign-birth and recent immigration, lack of acculturation and language barriers, which are associated with residence in these enclaves, contribute to lack of screening which can increase the rate of Cca [36–38]. Enclave was also associated with an increase of Cca cases in the Haitian community in Florida [39]. To our knowledge, this study is the first to determine the impact of the enclave on Cca incidence for the Asian and Hispanic community in California.…”
Section: Discussionmentioning
confidence: 93%
“…In South Florida, Haitian women living in the Little Haiti neighborhood of Miami experience the largest burden of cervical cancer in the region, with incidence rates that are higher than that of any other racial or ethnic minority (Kobetz et al, 2009; Kobetz et al, 2012). While the incidence of cervical cancer in the Miami metropolitan area is 9/100,000, the rate in in Little Haiti is over four times higher: 38/100,000 (Scarinci et al, 2010; Kobetz et al, 2011).…”
Section: Cervical Cancer Programming In Little Haiti Miamimentioning
confidence: 99%
“…Much of the formative research for the videos was generated through nearly ten years of work by Patne in Aksyon. This previous work indicated some important components to incorporate into the videos including: (i) discussing the association between HPV and cervical cancer; (ii) clarifying the difference between HPV and human immunodeficiency virus (HIV); (iii) addressing beliefs that the HPV vaccine is linked to sexual promiscuity; (iv) discussing the use of feminine hygiene practices; and (v) conveying the fact that HPV infections and cervical cancer can be asymptomatic (Barbee et al, 2010; Menard et al, 2010; Kobetz et al, 2011; Kobetz et al, 2012). …”
Section: Video Development and Filmingmentioning
confidence: 99%